Obstetrician–Gynecologists' Strategies to Address Vaccine Refusal Among Pregnant Women. Issue 1 (January 2019) - O'Leary, Sean T.; Riley, Laura E.; Lindley, Megan C.; Allison, Mandy A.; Albert, Alison P.; Fisher, Allison; Jiles, Angela J.; Crane, Lori A.; Hurley, Laura P.; Beaty, Brenda; Brtnikova, Michaela; Kempe, Allison
Abstract : OBJECTIVE: To describe 1) obstetrician–gynecologists' (ob-gyns') perceptions of the frequency of vaccine refusal among pregnant patients and perceived reasons for refusal and 2) ob-gyns' strategies used when encountering vaccine refusal and perceived effectiveness of those strategies. METHODS: We conducted an email and mail survey among a nationally representative network of ob-gyns from March 2016 to June 2016. RESULTS: The response rate was 69% (331/477). Health care providers perceived that pregnant women more commonly refused influenza vaccine than tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine: 62% of respondents reported 10% or greater of pregnant women they care for in a typical month refused influenza vaccine compared with 32% reporting this for Tdap vaccine. The most commonly reported reasons for vaccine refusal were patients' belief that influenza vaccine makes them sick (48%), belief they are unlikely to get a vaccine-preventable disease (38%), general worries about vaccines (32%), desire to maintain a natural pregnancy (31%), and concern that their child could develop autism as a result of maternal vaccination (25%). The most commonly reported strategies ob-gyns used to address refusal were stating that it is safe to receive vaccines in pregnancy (96%), explaining that not getting the vaccine puts the fetus or newborn at risk (90%), or that not getting the vaccine puts the pregnant woman's health at risk (84%). The strategy perceived as most effective was stating that not getting vaccinated puts the fetus or newborn at risk. CONCLUSION: Ob-gyns perceive vaccine refusal among pregnant women as common and refusal of influenza vaccine as more common than refusal of Tdap vaccine. Emphasizing the risk of disease to the fetus or newborn may be an effective strategy to increase vaccine uptake. Abstract : Obstetrician–gynecologists perceive vaccine refusal among pregnant women as common; emphasizing disease risk to the fetus or newborn may be an effective strategy to increase vaccine uptake.